Aloe vera: Magic or myth - Akhil Agarwal; Nidhi Dwivedi (Wolters Kluwer Medknow Publications, 2013)
Aloe vera is a versatile plant with a numerous health benefits. It has various outstanding features like anti-inflammatory, anti-bacterial, anti-viral and anti-tumor which help in accelerating wound healing and in treating various lesions of the oral cavity. Although it has clinically proven benefits, its practical use in repairing oral lesions still warrants further research. The A. vera plant, its properties, mechanism of action and clinical uses in dentistry are briefly reviewed in the current article.